THE EFFECT OF ADDING TOFU WASTE TO HYDROPONIC MEDIA ON THE GROWTH OF KANGKUNG (IPOMOEA AQUATICA) - Etty Indrawati; Abdul Chalim; Ratnaningsih Rukhiat; Olivia Seanders; Agus Purniawan; Eko Adhy Setiawan (Universitas Trisakti, 2023)
A team of lecturers from the Department of Environmental Engineering has researched waste treatment in quality, quantity, and operational terms in the tofu and tempeh industry and formulated a wastewater management model using appropriate and effective technology to support sustainable development. The results of processing tofu waste will be tested on vegetable plants with a hydroponic system. The problem is that the waste from the tofu industry pollutes the environment and is not utilized. This study aims to utilize liquid tofu waste as a hydroponic medium for vegetable plants. This research was carried out experimentally by making demonstration plots using a completely randomized design (CRD) method with three hydroponic media treatments and three replications. The three hydroponic media treatments were AB mix hydroponic media with the addition of 10% tofu waste which had been coagulated with moringa seed powder (Moringa oleifera); AB mix hydroponic media with the addition of 10% tofu waste which has been coagulated with tamarind seed powder (Tamarindus indica) and untreated AB mix hydroponic media. The plant growth factors to be measured are plant height and the number of leaves. The results showed that plant height and the number of leaves on Kangkung (water spinach, Ipomoea aquatica) treated with tofu waste, both coagulated moringa seed powder and tamarind seed powder, showed lower results than plants that were not treated. This can also be seen from the survival value of the treated Kangkung, which showed a value of 50% for the treatment of moringa seed powder and 67% for the treatment of tamarind seed powder. At the same time, the survival of the Kangkung plants that were not given treatment was 83%. It needs to be reviewed, especially from the BOD and COD values ​​of tofu waste solution, which are very influential on the growth of vegetable plants. It is necessary to do research again by fulfilling the nutritional requirements needed by plants to grow and thrive.